A Model of Waardenburg Syndrome Using Patient-Derived iPSCs With a SOX10 Mutation Displays Compromised Maturation and Function of the Neural Crest That Involves Inner Ear Development - Wen, Jie; Song, Jian; Bai, Yijiang; Liu, Yalan; Cai, Xinzhang; Mei, Lingyun; Ma, Lu; He, Chufeng; Feng, Yong (Frontiers in Cell and Developmental Biology, 2021)
Waardenburg syndrome (WS) is an autosomal dominant inherited disorder that is characterized by sensorineural hearing loss and abnormal pigmentation. SOX10 is one of its main pathogenicity genes. The generation of patient-specific induced pluripotent stem cells (iPSCs) is an efficient means to investigate the mechanisms of inherited human disease. In our work, we set up an iPSC line derived from a WS patient with SOX10 mutation and differentiated into neural crest cells (NCCs), a key cell type involved in inner ear development. Compared with control-derived iPSCs, the SOX10 mutant iPSCs showed significantly decreased efficiency of development and differentiation potential at the stage of NCCs. After that, we carried out high-throughput RNA-seq and evaluated the transcriptional misregulation at every stage. Transcriptome analysis of differentiated NCCs showed widespread gene expression alterations, and the differentially expressed genes (DEGs) were enriched in gene ontology terms of neuron migration, skeletal system development, and multicellular organism development, indicating that SOX10 has a pivotal part in the differentiation of NCCs. It's worth noting that, a significant enrichment among the nominal DEGs for genes implicated in inner ear development was found, as well as several genes connected to the inner ear morphogenesis. Based on the protein-protein interaction network, we chose four candidate genes that could be regulated by SOX10 in inner ear development, namely, BMP2, LGR5, GBX2, and GATA3. In conclusion, SOX10 deficiency in this WS subject had a significant impact on the gene expression patterns throughout NCC development in the iPSC model. The DEGs most significantly enriched in inner ear development and morphogenesis may assist in identifying the underlying basis for the inner ear malformation in subjects with WS.